Zhilong Huoxue Tongyu capsule alleviates myocardial fibrosis by improving endothelial cell dysfunction - Bi, Tao; Zhou, Yanan; Mao, Linshen; Liang, Pan; Liu, Jiali; Yang, Luyin; Ren, Guilin; Mazhar, Maryam; Shen, Hongping; Liu, Ping; Spáčil, Roman; Guo, Qing; et al. (Journal of traditional and complementary medicine, 2024)
BACKGROUND AND AIM: Zhilong Huoxue Tongyu (ZL) capsule is a classical traditional Chinese medicine (TCM) with satisfactory curative effects. Endothelial cell (EC) dysfunction plays an important role during myocardial fibrosis (MF). But the therapeutic effect of ZL capsule on EC dysfunction remains unknown in the development of MF. This study aims to investigate the effect of ZL capsule on EC dysfunction during MF in vivo. EXPERIMENTAL PROCEDURE: The model of MF is established in vivo by injecting isoproterenol for 14 days, simultaneously, we examined the therapeutic effect of ZL capsule on MF in vivo. An integrative approach combining biomarker examination, echocardiography and myocardial fibrosis condition using Hematoxylin-eosin staining, Masson staining, and Sirius red staining were performed to assess the efficacy of ZL capsule against MF. Subsequently, comprehensive immunofluorescence staining was performed to evaluate the therapeutic effect of ZL capsule on EC dysfunction. RESULTS AND CONCLUSION: Prior to experiments, analysis of the published single-cell sequencing data was performed and it was discovered that EC dysfunction plays an important role. Further pharmacological results showed that ZL capsule could alleviate fibrosis injury and collagen fiber deposition. The mechanism investigation results showed that the endothelial-to-mesenchymal transition (EndMT) and MHC class-II (MHC-II) expression in EC were improved. In addition, ZL capsule can attenuate the inflammatory response during MF by intervening the activation of CD4+T cell mediated by EC. For the first time, we provided evidence that ZL capsule could improve MF by alleviating EC dysfunction via the regulation of EndMT and expression of MHC-II. TAXONOMY CLASSIFICATION BY EVISE: Myocardial fibrosis, Chinese Herbal Medicine, Traditional Medicine, Endothelium, dysfunction, Endothelial-to-mesenchymal transition.
Keywords: Dysfunction; Transition; MHC; Capsule; Zhilong huoxue tongyu; Class-II; Myocardial; Endothelium; Endothelial-to-mesenchymal; Fibrosis